Study On Effect of Boron Carbide, Aluminium Oxide and Graphite On Dry Sliding Wear Behaviour of Aluminium Based Metal Matrix Composite at Different Temperature - BN, Sharath; C V, Venkatesh (Tribologia - Finnish Journal of Tribology, 2021)
The present research has been conducted to study the impact of boron carbide (B4C), aluminium oxide(Al2O3) and graphite on Aluminium 2219 (Al2219). According to current research, B4C and graphite material be a good substitute for Al2219.Reinforced composites and unreinforced Al2219 prepared by a stir casting process. A scanning electron microscope was used to analyze the reinforcement and distribution in the matrix and worn surface of the specimen. Exceptional wear resistance (30%) exhibited by B4C and graphite-reinforced hybrid composite at 150 ºC in contrast with the unreinforced Al2219. The B4C and Gr reinforcement particulate existence improves the strengthening kinetics in the matrix phase at 150 °C. The artificial neural network used to get the test significance, normalized factor importance and absolute relative error of less than 1%.